Analysis of Sincerity in the Spiritual Aspects of the Book Al-Ḥikam Ibn ‘Aṭā’illāh al-Iskandarī and Its Internalization in Islamic Education - Assidiq, Alwi Mubarok; Perawironegoro, Djamaluddin; Yoyo, Yoyo (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The rapid development of technology and information has created challenges in the educational world, particularly in the weakening of spiritual and moral dimensions in learning. Educational success is often measured primarily through cognitive achievement, while character and spiritual awareness receive less attention. This condition also affects Islamic education, which ideally integrates intellectual, moral, and spiritual development. In this context, the spiritual teachings contained in the book Al-Ḥikam by Ibn ‘Aṭā’illāh al-Iskandarī offer important insights regarding the value of sincerity (ikhlāṣ) as the inner foundation of human actions and spiritual growth. This study aims to analyze the value of sincerity in the spiritual teachings of Al-Ḥikam and to explore how this value can be internalized within the perspective of Sufism and Islamic education. The research employs a qualitative descriptive approach using content analysis to examine the meanings contained in selected aphorisms of Al-Ḥikam. The primary data source is the text of Al-Ḥikam, supported by secondary literature related to Sufism and Islamic education. Data were analyzed through stages of data reduction, categorization, interpretation, and triangulation to ensure the validity of findings. The results show that the value of sincerity in Al-Ḥikam, particularly in wisdoms 1, 9, and 10, emphasizes that the true value of deeds lies in the purity of intention rather than their outward form. Sincerity functions as the center of the spiritual journey, the foundation of moral formation and self-development, and the awareness of God's presence. Furthermore, the internalization of sincerity in Islamic education can be implemented through role modeling (uswah), habituation of positive actions, reflective practices (muhasabah), and strengthening intentions in learning.